DIVERSITY AND ABUNDANCE OF GASTROPODS IN KAWAL AND PENGUDANG BEACH, BINTAN REGENCY - Nisha Desfi Arianti; Mey Krisselni Sitompul (AQUASAINS, 2021)
Kawal Beach and Pengudang Beach are sandy beaches located in Bintan Regency, Kepualauan Riau Province. The two beaches have almost similar activities, is there are fishermen settlements. The difference is that Kawal Beach is located around beach tourism activities, while Pengudang Beach has no beach tourism activities. The purpose of this study was to understand how diversity and abundance gastropods in Kawal and Pengudang beach, then the similarity-based Bray-Curtis similarity in both locations. The method of determining the research location at Kawal Beach and Pengudang Beach is purposive sampling. The gastropod samples were collecting use transect with a quadrat of 1 m2 at the lowest tide zone along 100 meters toward the sea. They were taken by hand then put into a labeled zip lock plastic. Samples were then identified, documented and their diversity and abundance were calculated. A total of 42 species of gastropods were identified belonging to 15 families with an abundance index 3433 ind/m2 for Kawal Beach and 1564 ind/m2 for Pengudang Beach. Diversity of gastropods species are (H’) 1,83; (E) 0,5; and (C) 0,3 for Kawal Beach,  (H’) 2,55; (E) 0,7; and (C) 0,1 for Pengudang Beach. Bray-Curtis similarity shown is PK1-PP1=0,33; PK2-PP2 = 0,34; and PK3-PP3 = 0,15. This study is important in providing information on gastropods that live in the Kawal dan Pengudang beach. For future research should focus on temporal research in more depth to provide knowledge of gastropods communities and their ecological importance.